Design of Onboard Shunting Protection Software for Metro Engineering Vehicles Based on BeiDou Satellite Positioning System - LIU Hao; ZHANG Xu; YU Hechun (Kongzhi Yu Xinxi Jishu)
At present, metro engineering vehicles rely on visual driving by the driver, and there are safety problems such as rushing cross signals, overspeed and impacting switch in complex operation scenarios. This paper proposes a piece of shunting protection software based on the BeiDou satellite positioning system, and expounds its function design, software interface, mode conversion and protection method in detail. The shunting protection software uses safety computer platform tools, adopts modular design, and makes comprehensive use of the BeiDou satellite positioning system, beacon positioning system, computer-based interlocking system and binary tree theory to realize precise protection of metro engineering vehicles in shunting operation, effectively solve the safety risks in the operation process, and improve the safety of the metro engineering vehicles in shunting operation. At the end of 2020, the shunting protection software was tested in Guangzhou Metro Line 5 and Yuzhu Rolling Stock Depot.The results show that it can timely protect against rushing cross signals, overspeed and impacting switch, and meet the safety protection requirements of users for shunting operation.